Findings Across Practitioner Training Studies in Special Education: A Comprehensive Review and Meta-Analysis. (October 2017) - Brock, Matthew E.; Cannella-Malone, Helen I.; Seaman, Rachel L.; Andzik, Natalie R.; Schaefer, John M.; Page, E. Justin; Barczak, Mary A.; Dueker, Scott A.
Existing reviews address important questions about subsets of practitioner training studies in special education but leave important questions about the broader literature unanswered. In this comprehensive review, we identified 118 peer-reviewed single-case-design studies in which researchers tested the efficacy of practitioner training on implementation of educational practices to students with disabilities. We found publication of studies has proliferated in recent years, and most studies involved a multiple-baseline or multiple-probe design, researchers as training agents, in-service special education teachers or paraprofessionals as trainees, and students with learning disabilities or autism spectrum disorder as recipients of intervention. Through visual analysis, we detected 521 effects out of 626 opportunities across studies. The mean d -Hedges-Pustejovky-Shadish effect size was d = 2.48. Behavioral-skills training was associated with the most consistent improvement of implementation fidelity. We found statistically significant associations between implementation fidelity and modeling, written instructions for implementation, and verbal performance feedback.